Illustrated Manual of Pediatric Dermatology Diagnosis and Management - Mallory, Susan (Taylor & Francis, 2005)
Illustrated Manual of Pediatric Dermatology presents simple approaches to the problems that pediatricians and dermatologists see in their practices on a regular basis. Including approximately 300 color photographs to aid accurate diagnosis, this easy-to-use book provides a rapid reference guide to a broad range of pediatric and adolescent skin